1995
DOI: 10.1093/oxfordjournals.eurheartj.a060785
|View full text |Cite
|
Sign up to set email alerts
|

The importance of abnormalities of liver function tests in predicting mortality in chronic heart failure

Abstract: A number of simple clinical and laboratory variables were analysed in a group of patients with chronic heart failure to evaluate their prognostic significance. Five hundred and fifty-two patients were followed for a maximum of 13 years with a total exposure time to death or censored survival of 1148 years. Of the clinical variables, diuretic dose and NYHA class were related to mortality (P < 0.01), and ischaemic heart disease was associated with a worse prognosis than other aetiologies (P < 0.05). Of the labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 0 publications
2
77
2
2
Order By: Relevance
“…17) RV was ignored or not considered to be important, but recently, RV function has drawn more attention according to the increase in advanced HF. A number of studies have shown it to be a strong predictor of a poor prognosis in HF using the gold standard as RV ejection fraction (RVEF) estimated by cardiovascular magnetic resonance imaging (CMR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17) RV was ignored or not considered to be important, but recently, RV function has drawn more attention according to the increase in advanced HF. A number of studies have shown it to be a strong predictor of a poor prognosis in HF using the gold standard as RV ejection fraction (RVEF) estimated by cardiovascular magnetic resonance imaging (CMR).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise liver function tests were found to be abnormal only in patients with PH and RV dysfunction, reflecting either the greater hemodynamic derangement or, possibly, a longer duration of the RV overload. 54,55) Therefore, enlarged RVDd, which reveals RV dysfunction as determined using noninvasive methods and during emergencies, can be regarded as one of the LOS indicators, even in HF patients with LV dysfunction.…”
Section: )mentioning
confidence: 99%
“…68,69 The prognostic importance of abnormalities in liver function tests (LFTs) has varied among published studies. The unfavourable predictive value of abnormal LFTs has been described in patients with chronic HF 70 or acute decompensated heart failure (ADHF). 71 Total bilirubin was among the most highly significant predictors of mortality in a post hoc analysis of a large cohort of chronic HF patients in a clinical trial.…”
Section: Figurementioning
confidence: 99%
“…Low albumin reflecting poor nutrition is often seen in patients with cardiac cachexia [7][8][9]. LFTs have previously been characterized in patients with chronic heart failure and correlated to outcomes [10]; However to date no information exists on the correlation of abnormal LFTs at the time of diagnosis of heart failure secondary to left ventricular systolic dysfunction (LVSD) in the outpatient setting (OP) to patient outcomes. The purpose of this study was to characterize LFTs in a cohort of patients newly diagnosed with HFREF in OP and to explore the impact they have on patient outcomes.…”
Section: Introductionmentioning
confidence: 99%